Buckling analysis of functionally graded carbon nanotube-reinforced curved panels under axial compression and shear. (1st January 2017) - García-Macías, Enrique; Rodriguez-Tembleque, Luis; Castro-Triguero, Rafael; Sáez, Andrés
Abstract: The need for high-performance lightweight materials for the design of aerospace structures predicts a remarkable future role of carbon nanotubes (CNTs). In particular, thin curved fuselage panels are widely employed. However, the theoretical difficulties in the underlying differential problem induced by the curvature, as well as a still under development technology of CNT-based composites, the number of studies dealing with buckling behavior of this structural typology is limited. The present study aims to provide some insight into the linear buckling analysis of functionally graded carbon-nanotube reinforced (FG-CNTRC) cylindrical curved panels under compressive and shear loading. Effective properties of materials of the panels reinforced by single-walled carbon nanotubes (SWCNTs) are estimated through a micromechanical model based on either the Eshelby-Mori-Tanaka approach or the extended rule of mixtures. A series of numerical simulations have been carried out to inspect the influence of curvature, panel aspect ratio, the distribution profile of reinforcements (uniform and three non-uniform distributions) and CNTs orientation angle on the buckling critical load under compressive and shear loading in uniform thermal environments. Results demonstrate that the change of fiber orientation, CNTs distribution, panel aspect ratio, loading condition and temperature have noticeable effects on the buckling strength and buckling modes of FG-CNTRC curved panels. Highlights: Buckling of FG-CNTRC curved panels under compression and shear. Influence of fiber orientation on critical loads of FG-CNT cylindrical panels. Buckling behavior of FG-CNTRCs in uniform thermal environments. Analysis of negative/positive shear loading on buckling of curved FG-CNTRCs.